Effects of polymannuronate on performance, antioxidant capacity, immune status, cecal microflora, and volatile fatty acids in broiler chickens. (9th February 2015) - Zhu, Wenhui; Li, Defa; Wang, Jianhong; Wu, Hui; Xia, Xuan; Bi, Wanghua; Guan, Huashi; Zhang, Liying
Abstract : The aim of this study was to assess the effects of purified polymannuronate (PM) obtained from marine brown algae on the performance, antioxidant capacity, immune status, and cecal fermentation profile of broiler chickens. In a 42 d experiment, 540 (average BW 43.77 ± 1.29 g) 1-d-old Arbor Acres male broilers were randomly divided into 5 treatments with 6 replicates of 18 chicks and fed a corn and soybean meal (SBM)–based diet supplemented with 0, 1, 2, 3, or 4 g/kg polymannuronate. Adding polymannuronate to the broiler chickens' diets resulted in a significantly increased ADG and improved feed conversion compared with the control treatment. From d 1 to 42, the ADG of broilers fed 1, 2, 3, or 4 g/kg of polymannuronate was increased by 2.58, 4.33, 4.20, and 3.47%, respectively. Furthermore, parameters related to immune status, antioxidant capacity, and composition of the cecal microflora in broiler chickens fed the polymannuronate-containing diets were altered compared with broiler chickens fed a diet without polymannuronate. Supplementation with polymannuronate significantly increased the concentrations of lactic acid and acetic acid in the cecum compared with the control group. The results indicate that polymannuronate has the potential to improve broiler chicken immune status, antioxidant capacity, and performance.